Efektivitas Alokasi Dana Desa Kabupaten Solok Selatan Pada Tahun 2020 - Muhammad Habibi Ezyoni; Roni Ekha Putera (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This research describes the effectiveness of village fund allocation in South Solok Regency in 2020. The study method is carried out by analyzing primary and secondary data sources. In looking at the effectiveness of village fund management, it can be seen from five indicators, namely planning, organizing, implementing, and monitoring. The results showed that the allocation of village funds had been carried out optimally in accordance with applicable procedures. The allocation of village funds is carried out in accordance with operational functions from the planning stage until the results obtained are in accordance with the objectives. Planning is carried out by workshops, organizing is carried out in coordination with relevant stakeholders, implementation is carried out in an effective time and on target, supervision is carried out by BPKP in terms of allocation of village funds.